(untitled) (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: The present study was intended to demonstrate the role of Multidetector Computed Tomography (MDCT) in defining the extracardiac vascular abnormalities including the pulmonary arterial tree, Major Aortopulmonary Collateral Arteries (MAPCAs), patent ductus arteriosus (PDA), and detection of the common and uncommon findings in Fallot’s Tetralogy cases for proper pre-surgical evaluation. Methods: A retrospective review of all multidetector CT images acquired to evaluate suspected cases of Tetralogy of Fallot, presented at Ibrahim Cardiac Hospital & Research Institute between July 2017 and July 2018, was done. This comprised of a total of 35 cases who were examined by 64-slice MDCT. The patients were divided into four main groups: those with classic Tetralogy of Fallot with no associations, those with common associations, those with uncommon associations and those with a combination of common and uncommon associations. Results: In the present study, majority of the patients had levocardia (93.6%), situs solitus (96.9%) with none of the patients having either atrio-ventricular or arterio-ventricular discordance. Major findings of the patients were VSD (93.8%), right ventricular outflow tract obstruction (65%) with ventricular hypertrophy (75%). All patients had overriding of aorta with over 60% of the patients having 50% and 28% > 50% overriding. Approximately 3.1% of the patients had MPA atresia. MPA stenosis was detected in 93.3% of the cases. Conclusion: A customized approach to MDCT imaging improves the diagnostic accuracy and reduces unnecessary prolongation of the study and sedation times. A careful preoperative perception of the complex cardiovascular anatomy in patients with Tetralogy of Fallot aids in exposing the patients to a directed and prepared surgical approach. Ibrahim Card Med J 2019; 9 (1&2): 16-22